How Important is European Integration for Pro-European Voters in Times of Politicization? - Milena Rapp (Politische Vierteljahresschrift, 2024)
The increasing success of Eurosceptic parties and multiple European crises have fostered the politicization of European integration. However, we know little about how pro -European voters behave in this politicized environment. How important is European integration for pro-European voters? Do they care more about European integration when their vision of Europe is increasingly contested? The past 15 years have been characterized by persistent politicization of Eurosceptic parties and an increasing willingness of Europhile parties to engage with European topics. Moreover, European crises illustrated potential consequences of political disintegration. I expect these developments to be reflected in an increasing salience of European integration among pro-European voters. I derive salience estimates from spatial vote models encompassing four issue dimensions to track the development of salience. I use data from the European Social Survey, the European Election Studies, and the Chapel Hill Expert Survey, which cover many EU member states between 2008 and 2019. The results show that the salience of the European integration issue is most pronounced among Eurosceptic voters, while it is less pronounced among pro-European voters. However, in countries with a successful Eurosceptic party, it is more likely that the European integration issue also matters to pro-European voters. Moreover, there has been an increasing trend over time that European integration is not only important for anti- but also for pro-European voters across Europe. – – Der zunehmende Erfolg euroskeptischer Parteien und Europa bezogene Krisen haben die Politisierung der europäischen Integration vorangetrieben. Wir wissen jedoch wenig darüber, wie sich pro-europäisch eingestellte Wähler:innen in diesem politisierten Umfeld verhalten. Wie wichtig ist das Thema der europäischen Integration für pro-europäische Wähler:innen? Wird das Thema für sie wichtiger, wenn ihre Vorstellung von Europa zunehmend umstritten ist? Die letzten 15 Jahre waren durch eine anhaltende Politisierung durch euroskeptische Parteien und eine zunehmende Bereitschaft europhiler Parteien, sich mit europäischen Themen zu beschäftigen, geprägt. Darüber hinaus haben europäische Krisen die möglichen Folgen einer politischen Disintegration aufgezeigt. Ich erwarte, dass sich diese Entwicklungen in einer zunehmenden Bedeutung der europäischen Integration bei pro-europäischen Wähler:innen widerspiegelt. Ich schätze Salienzmaße mit räumlichen Wahlmodellen, die vier Themenbereiche umfassen, um die Entwicklung der Salienz zu erfassen. Ich verwende Daten aus dem European Social Survey, den European Election Studies und dem Chapel Hill Expert Survey, die eine Vielzahl von EU-Mitgliedstaaten zwischen 2008 und 2019 abdecken. Die Ergebnisse zeigen, dass die Bedeutung des Themas der europäischen Integration bei euroskeptischen Wähler:innen am stärksten ausgeprägt ist, während sie bei pro-europäischen Wähler:innen geringer ausfällt. Jedoch ist es in Ländern mit einer erfolgreichen euroskeptischen Partei wahrscheinlicher, dass europäische Integration auch für pro-europäische Wähler:innen von Bedeutung ist. Darüber hinaus ist ein zunehmender zeitlicher Trend zu beobachten, dass die europäische Integration nicht nur für euroskeptische, sondern auch für pro-europäische Wähler:innen wichtig ist.
Keywords: 320; Salience; European integration; Politicization; Pro-Europeanism; Salienz; Europäische Integration; Politisierung; Pro-Europäismus